Trends of surgical treatment for spinal degenerative disease in China: a cohort of 37,897 inpatients from 2003 to 2016 - Li Y (Dove Medical Press, 2019)
Yan Li,1,* Si Zheng,2,* Yunxia Wu,1,* Xiaoguang Liu,1 Gengding Dang,1 Yu Sun,1 Zhongqiang Chen,1 Jiayang Wang,2 Jiao Li,2 Zhongjun Liu1 1Department of Orthopaedics, Peking University Third Hospital, Beijing, China; 2Institute of Medical Information, Chinese Academy of Medical Sciences, Peking Union Medical College, Beijing, China *These authors contributed equally to this work Purpose: Given the aging Chinese population and the inevitable degenerative process of the spine, more elderly patients with spinal degenerative disease (SDD) are surgical candidates, placing a significant burden on health care resources. Few studies have investigated recent trends in hospital admissions and procedures for SDD in China. This study aimed to identify the trends, if any, in the number of surgical procedures undertaken for SDD in a large patient cohort.Materials and methods: This retrospective cohort analysis used data from inpatient medical records at Peking University Third Hospital between 2003 and 2016. Descriptive statistical analysis, regression models, and a Holt–Winters seasonal model were used to analyze trends.Results: Altogether, 38,676 surgery records from 37,897 SDD patients who had undergone surgical treatment were included in our study, among whom 49.60%, 47.81%, and 2.59% were treated because of cervical, lumbar, and thoracic degenerative disease, respectively. There was an increasing trend for spinal surgery performance with an increasing mean age at surgery, from 50.65 years of age in 2003 to 55.29 years in 2016. We also revealed interesting seasonal variation in our study – that is, most of the spinal procedures were performed during the winter and spring months.Conclusion: Our study showed a significantly increasing surgical workload for addressing SDD in China. Both the public and the health care system should be aware of this increase in chronic degenerative disease in the aging population. Keywords: spinal degenerative disease, surgical treatment, trends, seasonal variation